IMPLEMENTASI MODEL PEMBELAJARAN KANCING GEMERINCING UNTUK MENINGKATKAN KOSAKATA SISWA SEKOLAH DASAR DI SD GBI LAU GUMBA BERASTAGI - Sinabariba, Yessica Elisabeth; Sembiring, Friscilla; Perangin-angin, Aprita Melini Br. (Universitas Quality, 2023)
In the learning of vocabulary students have many differences from adults because adults will quickly absorb new words and easily concentrate their attention on the learning process, students need repetition in the absorption of vocabulary and are not yet able to concentrate. This research aims to improve the mastery of English vocabulary on family material through songs in students of V grade SD GBI Lau Gumba Berastagi. The mastery of vocabulary that is meant in this study is to read vocabulary, to write vocabularies and to understand vocabules. The subjects in this study were 30 V-class students at GBI Lau Gumba Berastagi. The method used is Class Action Research with research design according to Kemmis and Mc Taggart. The data collection methods used are tests, workpoints, observations and field records. The instruments used are student and teacher observation sheets, short filling sheets and field notes. The data analysis techniques used are quantitative descriptive. This research is worth looking at from previous research, reviewed from the still low vocabulary that elementary school students have. This research is done in support of a better and more exciting learning process.